The Role of Walangsungsang in the Formation of the Sultanate of Cirebon in the Early Period (1447-1479) - Fatimah Azzahra, Naswa; Subakti, Ganjar Eka (FALASIFA : Jurnal Studi Keislaman, 2024)
Cirebon City is a city located in the eastern part of West Java Province and is on the main coastal route. The Sultanate of Cirebon is known as one of the beginnings and influences of the spread of Islam in Java. Of course this cannot be separated from the role of Walangsungsang as its founder. And how Walangsungsang changed Cirebon which at that time was called Tegal Alang-Alang to become the Kingdom of Cirebon by Islamization and even built the Jalagrahan mosque which is now the oldest mosque in West Java. With his leadership he made Cirebon a kingdom that had a very good government system. Walangsungsang, who was known to be very patient, believed that building a kingdom did not have to use violence, bloodshed, and did not have to seize the kingdom or power of others.